Limitation of Environmental Organizations' Right to Sue Against Limited Production Forest Area : Case Study of Decision Number: 16/Pdt.G/LH/2023/PN.Bkn - Ekko Harjanto; Iwan Erar Joesoef; Irwan Triadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Environmental law enforcement provides space for environmental organizations to file lawsuits in the interests of environmental conservation as regulated in Article 92 of Law Number 32 of 2009 concerning Environmental Protection and Management. However, in practice, the right to sue environmental organizations is not always accepted by the courts, especially when it concerns certain areas such as Limited Production Forests. This study aims to analyze the material of environmental organizations' lawsuits based on Decree Number 16/PDT.G/LH/2023/PN.BKN. This study uses a normative juridical method and a case study approach with data sources in the form of court decision documents and related laws and regulations. The results of the study show that in this case, this Decision shows that it recognizes the active role of environmental organizations in supervising and suing permit applications for forest areas. In this case, the plaintiff organization argued that the defendant's actions in carrying out exploitation activities in the Limited Production Forest area had violated the law and harmed the ecological function of the forest, thus fulfilling the elements of an unlawful act as regulated in Article 1365 of the Civil Code. This finding resulted in an understanding of the analysis related to the material of the environmental organization's right to sue as an instrument of social control and supervision of forest area utilization policies.